Matching Strategy and Human Resources in Multinational Corporations - Edström, Anders; Lorange, Peter (Journal of International Business Studies, 1984)
Strategy is implemented by people; this article emphasizes this fundamental notion throughout. The characteristics of the major strategic levels and tasks in a multinational corporation (MNC) are identified, along with their implications for strategic human resource management. Through observations within 4 Swedish MNCs, the process by which human resources have gained a place in strategic management is examined. The experience of these firms in matching strategy and human resources is analyzed, concluding with suggestions regarding the implications of all this for practitioners and researchers.